Strategi Dakwah Pengurus Masjid Dalam Meningkatkan Shalat Subuh Berjamaah di Masjid Al-Hidayah Plaju Tangga Takat Palembang - Kadnezar, Niven; Ariadi, Purmansyah; R, Rulitawati (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to explore and analyze the da'wah strategies implemented by the management of Al-Hidayah Mosque in encouraging greater participation in congregational Fajr (Subuh) prayer. The declining attendance at Fajr prayer has become a significant concern, considering the high virtue and importance of this prayer in Islam. This study employs a qualitative descriptive method with a case study approach. Data were collected through observation, in-depth interviews with mosque administrators and congregants, as well as documentation. The findings indicate that the mosque management applies several da'wah strategies, including personal engagement with the community, regular Islamic lectures after Fajr prayer, motivational sermons, and the use of social media to disseminate mosque activities. These strategies have shown effectiveness in increasing awareness and participation among worshippers, although some challenges remain, such as individual lack of awareness and busy daily routines. This research is expected to contribute to the development of more effective mosque-based da'wah efforts that directly address community needs.